Assessing Environmental and Energetic Indexes in 27 European Countries - D'Adamo, Idiano; Gastaldi, Massimo; Rosa, Paolo (International Journal of Energy Economics and Policy, 2021)
The present work wants to assess the environmental and energetic sustainability of 27 European countries. To this aim, a Multi-criteria decision analysis and an analytical hierarchy process has been implemented to gather and process information from the experts. Results show that only four countries (Sweden, Denmark, Finland and Austria) present very significant performances. The intervention of policymakers must be clear, by penalizing non-responsible behavior, encouraging the development of circular and green practices, also through the exploitation of subsidies. A continuous monitoring of values over time and the identification of more appropriate criteria to evaluate performances, including economic and social views, are objectives to be addressed in the next future. Keywords: energy efficiency; greenhouse gas emissions; multicriteria analysis; renewable energy; sustainability; waste management JEL Classifications: Q20; Q40; Q50 DOI: https://doi.org/10.32479/ijeep.11169